GROWTH ACTIVITY TEST OF WHITE RAT HAIR COMBINATION OF CELERY (Apium Graveolens) LEAF EXTRACT AND GREEN GEDI (Abelmoschus Manihot) LEAF - Kawatu, Chelsea; Lebang, Julianri Sari; Jayanti, Meilani (Indonesian Biodiversity Journal, 2024)
Celery and Green Gedi leaves have been long considered traditional topical supplements to support hair growth. They contain flavanoids that are efficacious to induce keratinocyte proliferation. However, the research about whether the combination of celery and green gedi leaves can still provide an effect is limited. This current study aims to determine the effect of the combination of ethanol extracts of celery leaves and green gedi leaves on white rat hair growth. This is laboratory experimental research to compare the hair growth in three different groups with normal and positive control. Animals were randomly grouped (n=3 for each group) and then given a combination of leaf extracts and carbopol with a concentration of 17.5%:10%; 27.5%:15%;37.5%:20%. A normal control group was left untreated, while another group was treated with 2% minoxidil as positive control. The results of measuring fur weight on day 21 showed that the treatment group given the combination of extracts did affect the growth of rat hair. Statistical tests using one-way ANOVA showed a p-value of <0.001 which means there is a significant difference in the average hair weight of rats treated. LSD post hoc test showed that treatment with a 17.5%:10% concentration ratio was significantly different from the other treatments. It can be concluded that the combination of celery leaf extract and gedi leaf positively affects rat hair growth.